Development of Malaysian Science Standard Document for Teaching Year Four Student according to Neoteric Approach Curriculum: A Concept Paper - Ling, Ng Kai; Samsudin , Syakirah; Saad, Muhamad Ikhwan Mat; Daud, Anis Nazihah Mat; Rahim , Nurul Saidah Abdul; Arif , Harleny Abd; Jusoh , Normah (Journal of Education and Practice, 2024)
Purpose: This paper discussed about the development of Neoteric Approach Curriculum concept and the mapping of the Science Standard Document. The objectives of study are to examine the benefits of integrated curriculum, to outline the mapping of the concept of Neoteric Approach Curriculum for Year Four and to discuss the significant of integrating Science, Health Education and Visual Art. Methodology: The development of the Neoteric Approach Curriculum for Year 4 Science Standard Document was generated from the idea of subject-integration. The mapping of the integration of Science, Health Education and Visual Art are needed to originate an integrated discipline that named as Learning Cluster of Human Development for Year Four. This learning cluster is grouped based on the intention to improve human personal development in terms of skills development and academic knowledge. Findings: The Neoteric Approach is a new and modern approach for delivering the teaching and learning process that helps to strengthen the existing Malaysian National Curriculum. Neoteric Approach Curriculum acts as a solution to the modernization of education and pedagogy to produce a holistic student in terms of balanced physically, emotionally, spiritually and intellectually, as well as to be competitive to fulfil the needs of 21st century. The theories that supported the concept of Neoteric Approach curriculum are constructivism theory by Jean Piaget and progressivism theory by John Dewey. Based on the theories, the elements that emphasized are active learning and learning by doing which allows the students to learn by actively engage in the learning process and enhanced their learning experience. Unique contribution to theory, practice and policy: By having this approach, it could help to enhance the students-centred learning with integrated strategy and support active learning in classroom, cultivating students' knowledge and skills development which will benefit them in the future.